(untitled) (Innovaciones Educativas, 2021)
The right of each person to education is a transformative element in itself with the potential to transform the lives of individuals, communities and societies. There is a wide range of regulatory frameworks, declarations and commitments signed and assumed by the countries of the region. However, just mentioning the subject is not enough. The need for a not only political but also economic commitment and the financing of education so that the right to educational continuity of all people can be effectively guaranteed in an inclusive and equitable framework of quality education. In this sense, it is also important to highlight the comparative value that governance constitutes and its formidable educational impact effect by reinforcing the vital importance of adopting a rights-based approach based on non-discrimination, but above all, focused on equal access and permanence of the most vulnerable groups.